Evaluation of the productive and reproductive performance of sexual precocity at different ages in Nellore heifers - Mota, Lucio F.M. [UNESP]; Arikawa, Leonardo M. [UNESP]; Nasner, Sindy L.C. [UNESP]; Schmidt, Patrícia I. [UNESP]; Carvalheiro, Roberto [UNESP]; Oliveira, Henrique N. [UNESP]; Albuquerque, Lucia G. [UNESP] (Elsevier, 2024)
This study aimed to investigate the differences between productive and reproductive performance traits of sexually precocious and non-sexually precocious Nellore heifers and to evaluate the genetic correlation of sexual precocity with traits of economic importance. For this purpose, 300,000 Nellore heifers were evaluated for reproductive traits: heifer pregnancy (HP) at 14 (HP14), 18 (HP18), and 24 (HP24) months; heifer rebreeding (HR); number of progenies up to 53 months (NP53); and probability of the cow remaining in the herd until 76 months with at least 3 progenies (Stay). The growth-related traits evaluated included female yearling weight (YW); average daily gain from weaning to yearling (ADGW-Y); weight at maturity (MW); weaning weight of first progeny (WWprog); and female visual scores at yearling for conformation (Conf), precocity (Prec) and muscling (Musc). The effects of female YW and ADGW-Y in six categories on HP14, HP18, and HP24 were analyzed using Generalized linear mixed models (GLMM). Furthermore, a linear mixed model was used to evaluate the impact of HP on WWprog, MW, and reproductive performance (NP53 and Stay). Genetic correlations of HP evaluated in different months with growth and reproductive traits were estimated using a bivariate animal model. Precocious heifers (HP14) were lighter for YW and MW but had greater ADGW-Y than HP18 and HP24. The probability for HP14, HP18, and HP24 increased as the classes of YW and ADGW-Y increased. However, heifers weighing more than 326 kg had a slight reduction in the probability of becoming pregnant at HP14 and HP18. Precocious heifers (HP14 and HP18) produced their first progeny by 3 % lighter than HP24, although they had a greater NP53. Precocious heifers at 18 months (HP18) were 3 % and 6.8 % more likely to remain in the herd than HP14 and HP24 heifers, respectively. Genetic correlations between growth traits (WW, YW, ADGW-Y, and MW) and heifer pregnancy (HP14, HP18, and HP24) ranged from weak (rg = 0.27 ± 0.05) to moderate (rg = −0.47 ± 0.07). The genetic correlation between HR and HP was stronger for HP24 (0.75) against HP14 (0.58) and HP18 (0.64). Although, the genetic correlation between NP53 and Stay with HP14 was higher (rg = 0.53 and 0.45) than those observed for HP18 (rg = 0.46 and 0.38) and HP24 (rg = 0.35 and 0.39). The genetic correlation estimates between HP and visual scores were moderate and favorable for HP14. Selecting HP14 is beneficial for production systems because it increases the NP53 during the productive life without compromising heifer productivity or reproductive performance. However, attention should be given to improving the HR of heifers who become pregnant early.
Keywords: Bayesian inference; Beef cattle; Genetic correlation; Growth traits; Number of progenies; Sexual precocity; Weight gain